Implementasi Sekolah Lapang Iklim dan Dosis Pupuk Terhadap Karakter Kimia Tanah dan Hasil Jagung - Rifqi Ramadhani; Komariah Komariah; Sumani Sumani; Dwi Priyo Ariyanto (Universitas Sebelas Maret, 2018)
Indonesian Agency for Meteorology Climatology and Geophysics Agency (BMKG) stated that the implementation of CFS program can increase the production significantly up to 30% (BMKG 2016). This research was conducted to know the influence of climate field school (CFS) and fertilizer dosage on soil chemical properties and corn yield. The study was conducted with a nested experimental design with two factors. Factor A has two levels: CFS Program (S1) and nonCFS (S2) and factor B was fertilizer dose. Factor B is nested on factor A as A (B). The fertilizer dose factor consists of 6 levels; T0 (without fertilizer); T1 (100% organic fertilizer); T2 (75% organic + 25% inorganic fertilizer); T3 (50% organic + 50% inorganic fertilizer), T4 (25% organic + 75% inorganic fertilizer), T5 (100% inorganic fertilizer). The results showed that CFS program increased available P, available K and soil pH, while fertilizer dose (50% organic fertilizer + 50% inorganic fertilizer) on CFS program yielded the highest soil organic matter (4.12%). CFS and fertilizer dose both did not affect the yield of maize significantly. However, the average yield of maize on CFS land is greater (6.50 tonha-1) compared to nonCFS (5.38 tonha-1). The treatment with 100% inorganic fertilizers) on CFS program gives highest yield (8.75 tonha-1).